New climate investments must strengthen sustainable development and minimize trade-offs - Stephan Hoch; Britta Horstmann; Axel Michaelowa; Jonas Hein (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The impacts of global warming threaten to undermine the core objectives of sustainable development: Large-scale invest¬ments that aim to reduce greenhouse gases (GHG) are indispensable. A just low-carbon transformation requires that mitigation investments seek to generate sustainable develop¬ment (SD) benefits while also minimizing their adverse effects. A central goal of the United Nations Framework Convention on Climate Change (UNFCCC) is alignment of the climate and the sustainable development agendas. Govern¬ance and operational structures of policy instruments and funds should attempt to prevent local communities being confronted with the impacts of both climate change and climate protection measures. Ongoing negotiations of the rules governing post-2020 climate protection measures offer the opportunity to address these issues. This briefing paper begins by analysing how activities under the Clean Develop¬ment Mechanism (CDM) both positively and negatively impact sustainable develop¬ment. It then compares these experiences with emerging climate governance approaches by examining the Warsaw Frame¬work for Reducing Emissions from Deforestation and Forest Degradation (REDD+) and the Green Climate Fund (GCF). Key conclusions: Activities under the CDM have both positively and nega¬tively affected sustainable development, depending on the type and local circumstances: Community-based activities regarding energy access reap high benefits for sustainable development and large-scale hydropower and reforesta¬tion projects can create negative impacts. The CDM requires stakeholders to be consulted at the beginning of the project design but does not include international safeguards to prevent ongoing activities harming local communities. More recent financing instruments and investment frame¬works such as the GCF and REDD+ have begun to formu¬late additional regulatory frameworks to promote sustain¬able development and avoid harmful side effects. While these frameworks still must be tested in practice, the GCF stipulates verification of sustainable develop¬ment impact and mechanisms for independent redress. The future of a reformed CDM for financing climate protection and sustainable development depends on political decisions. However, the CDM offers critical in¬sights for designing a new generation of multilateral cli¬mate finance mechanisms. Post-2020 mechanisms should create strong and harmonized standards to help align the sustainable development agenda with climate protection. While sustainable development and climate goals can be mutually reinforcing, there may be trade-offs between these agendas. Future climate finance mechan¬isms should minimize trade-offs and allow for appeals by vulnerable communities affected by investments in climate protection.
Keywords: 330; Klimawandel; Agenda 2030